2014
DOI: 10.1136/bcr-2014-011233
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of pituitary function following treatment of an unruptured giant cavernous carotid aneurysm using Surpass flow-diverting stents

Abstract: Giant aneurysms arising from the cavernous internal carotid artery (ICA) can mimic pituitary adenomas and may cause pituitary dysfunction due to their mass effect on the pituitary gland. We report a case of a 56-year-old man presenting with impotence, fatigue and panhypopituitarism who was found to have a giant unruptured aneurysm arising from the right cavernous ICA with severe mass effect on the pituitary gland. The patient underwent endovascular treatment of the giant aneurysm using two telescoping Surpass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…However, the endovascular coil embolization has been developed and is now available for application. Good occlusion of the aneurysm and partial recovery of the pituitary function has been reported in some cases of middle-aged and elderly patients (13,14). The accumulation of more details on cases of hypopituitarism due to intrasellar aneurysms will be required in order to clarify the treatment and nature of this disease.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the endovascular coil embolization has been developed and is now available for application. Good occlusion of the aneurysm and partial recovery of the pituitary function has been reported in some cases of middle-aged and elderly patients (13,14). The accumulation of more details on cases of hypopituitarism due to intrasellar aneurysms will be required in order to clarify the treatment and nature of this disease.…”
Section: Discussionmentioning
confidence: 96%
“…Open surgery methods are hazardous and technically challenging (10). In addition, hypopituitarism is usually permanent, and improvement of the pituitary function is difficult to achieve, even after surgery (11,12). Therefore, hormone replacement therapy is required even after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] The mechanisms of endocrine dysfunction may involve either mechanical compression of the pituitary gland and stalk, or vascular compression of the artery supplying the pituitary gland resulting in pituitary ischemia. [ 26 27 ] Our present patient was first treated under a diagnosis of depression associated with hyponatremia induced by secondary adrenal insufficiency. Subsequently, our patient was referred to our hospital after discovery of the intracranial mass suggestive of tumor.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 11 ] Recently, flow diverting stents have offered treatment for formidable and complex aneurysms, but previous trials showed complete aneurysm occlusion of 73.6% at 6 months and 86.8% at 1 year, and 5.6% had major complications such as major ipsilateral thrombosis, intraparenchymal hemorrhage, and neurologic death. [ 2 3 ] Good occlusion of the aneurysm and recovery of pituitary function was reported in one case,[ 26 ] but pituitary hormone replacement therapy was necessary after aneurysm treatment in another case. [ 5 ] Delayed pan-hypopituitarism was observed after treatment of ICA aneurysm with flow diverting stent, partly caused by compromise to the blood supply of the pituitary gland as a result of the flow diversion to the ICA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation